The association between ambient air pollution and cardiorespiratory health outcomes of adults residing in informal settlements of the Western Cape in a 12 month period - Allie, Tasneem (Department of Public Health and Family Medicine, 2025)
Background: There is limited data on the association between ambient air pollution cardiorespiratory outcomes among adults especially among populations with low socio-economic status in low- and middle income countries. Objectives: A cross-sectional cohort study was conducted in four informal settlements of the Western Cape to determine the association between annual NO2 and PM2.5 air pollution exposure and cardiorespiratory outcomes in adults. Methods: A questionnaire was administered to 506 participants who were guardians of learners in a primary study, to collect information on cardio-respiratory symptoms and relevant covariates. Land use regression modelling in R was used to estimate the annual average PM2.5 and NO2 exposure at each household. Cardio-respiratory outcomes included wheezing in the last 12 months, doctor diagnosed asthma, asthma symptoms score (calculated as the sum of positive responses to 3 asthma questions), chest pain, hypertension and hypercholesterolaemia. The quantile g computation package in R was used to assess the joint-effect of PM2.5 and NO2 on the outcome of interest. A concentration curve was determined, while adjusting for confounders (paraffin exposure, mould exposure, smoke exposure, low education, unemployed, sex and age). Results: Most of the participants were female (89.9%), with a median age of 40 (IQR=12.8). The annual median concentration of PM2,5 9.8 μg/m3 and NO2 was 16.86 μg/m3 , below the National Ambient Air Quality Standards (NAAQS) There was positive association between NO2 and shortness of breath on exertion (OR:4.02, 95% CI:2.21-7.65) adjusting for PM2,5 and other confounders. There were no other significant associations found between PM2.5 and NO2 levels and other cardiorespiratory outcomes including indoor air pollution. The concentration curve indicates an increased risk in self-reported shortness of breath on exertion with increasing NO2 concentrations above 10μg/m3 . Conclusion: The study found evidence of an association between annual NO2 and shortness of breath on exertion. The study also provides policy-relevant information from the concentration-response curve in demonstrating elevated risk at a level four-times lower than the current National Ambient Air Quality Standard (NAAQS) of 40µg/m3 . This indicates that the NAAQS should be more in keeping with the WHO Ambient Air Quality guidelines for NO2 at 10 μg/m3 and lower in low- and middle-income countries where underlying susceptibility may increase the observed risk.